Development of Natural Acid-Base Indicators Based on Biocellulose in Grade XI Science at MAN 1 Kubu Raya - Fitriani, Melda; Kurniati, Tuti; Kurniawan, Rizmahardian Ashari; Mukhlishin, Hamdil (FKIP UM Pontianak, 2024)
The learning of chemistry requires practical activities to assist students in understanding chemical concepts deeply and also to connect scientific principles with everyday life. However, practical activities often face challenges such as inadequate equipment and materials in laboratories, posing a challenge for educators to conduct practical-based learning. This article proposes the development of natural pH indicators based on bacterial cellulose to enhance acid-base learning in schools. These natural pH indicators are formulated by combining plant-based natural indicators with (Biocellulose) and immersing them in buffer solutions ranging from pH 1 to 14. The color changes produced by these natural pH indicators based on bacterial cellulose indicate different pH levels, serving as a reference for each solution measurement.These indicators are used in classroom learning during acid-base topics in the 11th-grade science classes. Stimulates curiosity and interest among teachers and students, leading to more engaged observations during the experiments.Overall, teachers and students perceive these natural pH indicators based on bacterial cellulose as effective tools for conveying acid-base concepts and enhancing engagement in practical-based learning methods.